Multidimensional inequality and COVID-19 in Brazil - Luiza Nassif Pires; Laura Carvalho; Eduardo Rawet (Levy Economics Institute of Bard College, 2020)
After spending over 6 percent of GDP responding to the COVID-19 crisis, Brazil has suffered among the worst per capita numbers in the world in terms of cases and deaths. In this policy brief, Luiza Nassif-Pires, Laura Carvalho, and Eduardo Rawet explore how stark inequalities along racial, regional, and class lines can help account for why the pandemic has had such a damaging impact on Brazil. Although they find that fiscal policy measures have so far neutralized the impact of the crisis with respect to income inequality, the existence of structural inequalities along racial lines in particular have resulted in an unequally shared public health burden. Broader policy changes are necessary for addressing dimensions of inequality that are rooted in structural racism.
Keywords: 330; Coronavirus; Soziale Ungleichheit; Ethnische Gruppe; Einkommensverteilung; Brasilien